Facelets Essentials Guide to JavaServer Faces View Definition Framework - Aranda, Bruno; Wadia, Zubin (Apress : Imprint: Apress, 2008)
Facelets is a templating language developed from the ground up with JavaServer Faces in mind. Created in response to the many concerns involving JavaServer Pages (JSP) when building JavaServer Faces (JSF) views, Facelets steps outside of the JSP specification and provides a highly performant, JSF-centric view technology. Facelets' top properties, templating, reuse, and ease of development, allow it to help making JSF a technology suitable for large-scale projects. One of the first things a developer using Facelets finds is that it immediately leads to a reduction in user interface code. Facelets Essentials, the first book on Facelets, introduces you to its importance, architecture, and relationship to JSF and the Apache MyFaces web framework. Learn to create your first application using the power and flexibility Facelets offers. Then, master and apply its basic and advanced features including Unified Expression Language, templating and reuse, custom tag development, and more.